2021
DOI: 10.3390/pathogens10020194
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Dermatophyte Fungi by Australian Jarrah Honey

Abstract: Superficial dermatophyte infections, commonly known as tineas, are the most prevalent fungal ailment and are increasing in incidence, leading to an interest in alternative treatments. Many floral honeys possess antimicrobial activity due to high sugar, low pH, and the production of hydrogen peroxide (H2O2) from the activity of the bee-derived enzyme glucose oxidase. Australian jarrah (Eucalyptus marginata) honey produces particularly high levels of H2O2 and has been found to be potently antifungal. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Oxidative stress was measured in drug-treated T. rubrum using ROS-sensitive indicator DCFDA as described previously (34). Coverslips with drug-treated T. rubrum R-218 hyphae were prepared as described above.…”
Section: Quantification Of Intracellular Rosmentioning
confidence: 99%
“…Oxidative stress was measured in drug-treated T. rubrum using ROS-sensitive indicator DCFDA as described previously (34). Coverslips with drug-treated T. rubrum R-218 hyphae were prepared as described above.…”
Section: Quantification Of Intracellular Rosmentioning
confidence: 99%
“…Several in vitro and in vivo studies and researches have been conducted on the properties of honey: antibacterial, antifungal, antiviral and antiprotozoal (Mohammed et al 2017;Rani et al 2017;Semprini et al 2018;Guttentag et al 2021). The antimicrobial potential of honey varies considerably, it mostly depends on the botanical origin of the flowers, geographic source, season, harvest, storage conditions (Irish et al 2011;Anthimidou and Mossialos 2013), age and the health of bee colonies (Ibarguren et al 2010;Aween et al 2012a;Mathialagan et al 2018).…”
Section: Properties Of Honeymentioning
confidence: 99%
“…Mulu et al (2010) stated that Ethiopian honey treated the resistant strains of C. albicans in HIV-positive patients. Guttentag et al (2021) disclosed in their in vitro assays that Australian honey (Table 1) inhibits conidial germination and damages the structure of hyphae in Trichophyton rubrum. Some Egyptian single--flower honeys (Table 1) have shown some antifungal and antimycotic properties against Epidermophyton species, Trichosporon and Microsporum (El-Gendy 2010).…”
Section: Properties Of Honeymentioning
confidence: 99%
“…Furthermore, this variety of honey is considered to be a biofilm reducer for Candida species at concentrations that range between 50% and 75% (w/v). Further relevant academic work has suggested that the production of H 2 O 2 is critical for the antifungal activity of honey, but still not sufficient, as its level in honey's composition was too low to manifest a potent activity against some pathogenic fungi [180]. This can lead us to the conclusion that there are other compounds that act may as enhancing factors for the observed antifungal activity.…”
Section: Antifungal Effectsmentioning
confidence: 99%